A invenção das subjetividades nos mercados da pacificação: um estudo sobre os empreendedores da Favela Turística/RJ - Damas, Helton Luiz Gonçalves (2018)
The main objective of this study was to understand the contemporary regime of subjectivity in the favelas of Rio de Janeiro, based on the analysis of the processes that involve the pacification of these territories and the emergence of new forms of the market, having as empirical cut, the "tourist favela" and the "Self-management". The pacification project represented a possibility of political and economic management of certain territories chosen according to the strategic objectives defined by the power apparatus. Control, militarized surveillance and the consequent domestication of bodies can not be considered the only forms by which power invested, since pacification also sought to structure a field of action in which the favelado itself was an active subject of its own transformation by the way of entrepreneurship. In this sense, the study sought to understand the process of subjectivation of slum dwellers as something situated in the midst of a complex of apparatuses, practices, machinations and compositions within which they were constituted and which presupposes the implication of particular relations with themselves, the research analyzed how the intersections between a set of devices that propitiated a strategic articulation of the ways of conduct of others with the forms of self-government. In order to elaborate the study, the following areas of UPP were taken as object of analysis: Favela Santa Marta, Favela Pavão-Pavãozinho, Ladeira dos Tabajaras / Morro dos Cabritos and Complexo do Alemão. The methodology used for the purposes of the thesis could be fulfilled consisted in the elaboration of a study based on the qualitative analysis, obtaining data through direct observations and semi-structured interviews. As a result, it was possible to observe that the expansion of neoliberal logic in the pacified favelas, on the one hand, configured entrepreneurship as a possibility for the favelados to find their "place in the sun" and on the other intensified processes related to the individualization of destiny and poor subject, as well as the emptying of the public sphere and collective projects.